Understanding the Interaction of Outdoor Recreation Motivation, Serious Leisure Perspective and Environmental Concern: A Study of Park Visitors - Heidari, Kolsoum (Université d'Ottawa | University of Ottawa, 2025)
This doctoral thesis investigates the relationship between leisure engagement, motivation, and environmental concern among visitors to Gatineau Park, Canada. Grounded in the Serious Leisure Perspective (SLP), Self-Determination Theory (SDT), and environmental concern literature, the research explores how different forms of park-based recreation—casual, project-based, and serious—are linked to motivational patterns and ecological awareness. Study 1 used structural equation modeling (SmartPLS) on survey data from 248 participants, revealing that serious leisure engagement significantly predicted environmental concern (R² = 0.563), particularly in areas like balance of nature (β = 0.771) and ecological crisis (β = 0.766). Younger, educated individuals showed higher ecological sensitivity, emphasizing leisure’s role in fostering environmental stewardship. Study 2 applied Two-Step Cluster Analysis to identify three main visitor types—Casual, Transitional, and Committed—along with five subgroups within the transitional category. This highlighted the fluid and developmental nature of leisure commitment, influenced by factors such as gender, income, and education. Findings offer actionable insights for park management in designing inclusive, responsive programs. Study 3 involved 23 interviews and identified distinct motivations among serious, casual, and project-based visitors. Serious participants emphasized emotional resilience and identity, casual users prioritized relaxation, and project-based participants combined episodic engagement with learning or goal orientation. Motivation was dynamic and context-driven across all types. Overall, the thesis proposes a “leisure engagement pathway” illustrating how deepening park involvement can nurture environmental awareness. The findings contribute to leisure theory and offer practical strategies for creating sustainable, user-centered park experiences.
Keywords: Serious Leisure Perspective; Environmental Concern; Outdoor Recreation; Motivation; Self-Determination Theory; Visitor Segmentation; Gatineau Park; Mixed Methods; Park Management